Imaging studies and indications for surgical treatment of carotid spondylosis - Piotr Porzych; Krystyna Nowacka; Karol Ogurkowski; Joanna Simińska; Magdalena Hagner-Derengowska; Dorota Ratuszek-Sadowska; Wojciech Hagner (Kazimierz Wielki University, 2017)
Spondylosis cervical spine, is the result of a complex process which occurs in the course of normal physiological aging body tissues. This lengthy process progresses normally for decades. It is believed that it is initiated early degenerative changes in the intervertebral discs. Surgical treatment of only a part of the treatment and never correspond to the whole patient's expectations. Alleviates or eliminates direct threat to life or loss of health, not solving the drug problem as a whole. Before planning surgery, are widely used imaging. It is important to remember that radiological signs of wear of the cervical spine, does not always correspond to the clinical manifestations.